Analisis kepatahan ke atas vertebra lumbar tulang belakang menggunakan kaedah unsur terhingga dan monte carlo - Zulkifli, Ahmad@Manap (2012)
The lumbar vertebra 4s a, segment of the human spine that is commonly used during daily life. This consequently leads to a vertebral fracture and subsequent a low back pain. Low back pain is a top of musculoskeletal disorder and serious health problem. These problems are due to the heavy work, lifting and sudden forceful incidents. Furthermore, osteoporosis and bone fracture are related and most attention has been given to vertebral fractures. This disease described by loss of bone mass and increased the risk to fracture. The main objective of this work is to develop cracked structure of the lumbar vertebra model from image processing data using finite element modeling associated Monte Carlo methods. In nature, uncertainties play a critical role in understanding the vertebra injury on the cracked structure. The methodology comprises the lumbar vertebra modeling, uncertainties of cracked structure sampling, generate meshing technique, and probabilistic using Monte Carlo simulation. There are two types of model have been developed for this study; model for stress concentration (MPT), and model for crack structure (MSR). The function of MPT is to investigate the effect of critical stress subjected to the model whereas MSR is to simulate the cracked structure using finite element and probabilistic analysis. Meshing technique is generated as mapped mesh for cracked structure while a free mesh with suitable consideration to the whole body of vertebra. Since the vertebra is a brittle material, fracture criterions are based upon on the stress intensity factor for linear elastic fracture mechanics (LEFM). In order to operating the uncertainties of cracked structures sampling parameter, probabilistic analysis can be used to evaluate the probability of failure model when associated with the finite element analysis. Anatomical parameter of the model input variables is accounted by modeling these parameters as random variables caused a failure in vertebra structure are geometry, material properties and loading using Monte Carlo technique. The maximum stress was observed on the pedicle region with 2.2 MPa. This condition is weakening that area and tends to be fracture. There are 100 samples were recommended to obtain reasonable accurate point estimates and only 1% will be fail due to the applied stress exceeds the yield stress or material resistance. On the other hand, stress intensity factor (SIF) of opening mode become the most dominant compared to the shearing and tearing modes with 0.52 MPa'Im. In addition, sensitivity analysis was revealed that the force applied to the vertebral body and crack size parameters give a huge correlation with output response. In conclusion, the crack structure study on pedicle is useful to investigate the fracture characteristics phenomena in physiological loading.